Supramolecular-controlled regioselective photochemical [4 + 4] cycloaddition within Cp*Rh-based metallarectangles. Issue 22 (25th May 2022) - Bai, Sha; Wang, Li-Feng; Wu, Zhen-Wei; Feng, Ting; Han, Ying-Feng
Abstract : A regioselective and reversible photochemical [4 + 4] cycloaddition was achieved within supramolecular metallarectangles with the assistance of a Cp*Rh-based organometallic template. Abstract : Photochemical reactions are vital synthetic means for the synthesis of natural products and highly strained molecules. However, it remains an immense challenge to control the chemo- and regioselectivity in the photoreactions of anthracene derivatives while maintaining high reactivity. Herein, we report the synthesis of two photoactive metallarectangles 1a and 1b by coordination-driven self-assembly of 2, 6- and 2, 7-bifunctionalized anthracenes with a half-sandwich rhodium template. By taking advantage of the rhodium template, the anthracene groups within the metallarectangles can be preorganized in a parallel fashion and exclusively undergo a photochemical [4 + 4] cycloaddition. As a result, the syn -photodimers were obtained in quantitative yields under irradiation at 365 nm. The photocycloaddition of metallarectangles 1a and 1b was found to be reversible via photo- and thermal cleavage reactions, even after repeating three times. Furthermore, pure organic photodimers 3a and 3b, which are difficult to synthesize by conventional organic methods, can be readily dissociated from the metalloassemblies in high yields.